Synthetically useful metal-mediated radical transformations in water and aqueous media - Postigo, Al; Nudelman, Norma Sbarbati (Coordination chemistry reviews, 2011)
[Display omitted] ► Metal-mediated radical organic modifications are obtained in water or aqueous media. ► The environmental impact in the use of metals is reduced in aqueous media and water. ► Atom-efficiency mediated by metal radicals lead to synthetically useful products. ► Thus, alkylation and allylation reactions of multiplebonds can be obtained. ► Metal-mediated cyclizations in water proceed stereoselectively and efficiently. In this review non-carbon-centered radicals are used in water and aqueous mixtures to induce and accomplish several synthetically useful organic transformations such as Reformatsky reactions, alkylation and allylation reactions of carbonyl compounds, electron deficient alkenes and imine derivatives, radical conjugate additions, metal-mediated radical cyclizations, reductive cross coupling reactions and other coupling reactions, oxidation and reduction reactions in water. In doing so, the array of metal radicals used encompass elements from the main groups (IIIB, IVB, VB and VIB groups), as well as transition metals. However, the important class of radical hydrometallation reactions of carbon–carbon multiple bonds in water is not the subject of this work.